The path to peace and democracy: the case of Timor-Leste - Jose Cornelio Guterres; Jose Cornelio Guterres; Roberta Holanda Maschietto (Frontiers in Political Science, 2025)
This study explores the development and challenges of democracy in Timor-Leste, one of the youngest democracies globally, following the restoration of independence in 2002. It examines how historical legacies of Portuguese colonialism and Indonesian occupation, combined with international interventions, have shaped the country’s democratic evolution in the context of peace and state-building. The analysis is based on a comprehensive literature review, and considers key factors influencing democratic consolidation. We highlight that Timor-Leste has reached significant milestones in the field of democracy—such as free and fair elections, constitutional safeguards, and active civil society—and represents a successful case of democratisation in the context of peacebuilding. That said, further progress is pending on: a better integration between formal and informal governance structures, overcoming political patronage, and on better results in terms of social and economic inclusion, especially vis-à-vis the youth and rural population.